Inovasi Dalam pengelolaan Greenhouse untuk Meningkatkan Keberhasilan Budidaya Cabai Lombok pada Usaha Pertanian BUMDes - Sulaiman Sulaiman (Ta'amul: Journal of Islamic Economics, 2026)
Lombok chili (Capsicum annuum L.) is one of Indonesia’s leading horticultural commodities with high economic value and an important role in supporting food security and rural livelihoods. However, its productivity is often constrained by climate variability, limited water availability, pest attacks, and the low adoption of modern cultivation technologies. This study aimed to analyze the effectiveness of greenhouse innovation in improving the cultivation performance of Lombok chili in the agricultural business unit of a Village-Owned Enterprise (BUMDes). For illustration purposes, this study employed an empirical quantitative approach with an observational design involving 60 chili plants divided into two treatment groups: greenhouse cultivation and open-field cultivation, over a period of 12 weeks. The observed parameters included plant height, leaf number, temperature, humidity, and fruit yield per plant. Data were analyzed using an independent samples t-test at a 5% significance level. As an illustrative example, the results showed that chili plants cultivated in the greenhouse achieved an average plant height of 68.4 ± 5.3 cm, significantly higher than those grown in the open field (55.7 ± 6.1 cm, p < 0.001). The average number of leaves increased by 24.8%, while fruit yield per plant increased from 31.6 ± 4.8 to 42.9 ± 5.5 fruits, representing an improvement of approximately 35.8% compared with conventional cultivation (p < 0.05). The implementation of a greenhouse system equipped with drip irrigation, temperature and humidity monitoring, and liquid organic fertilizer application created a more stable microclimate, thereby enhancing vegetative growth and crop productivity. These findings indicate that greenhouse innovation has strong potential as an effective and sustainable cultivation strategy to support technology-based agricultural development in Village-Owned Enterprises (BUMDes).